Alternative concepts to identify the characteristics of vocational technology education curriculum - Utari, Nadia; Mukhaiyar, Riki (Jurnal Pendidikan Teknologi Kejuruan, 2020)
Higher education is expected to produce excellent graduates to meet the needs of educated and skilled personnel in the era of industry 4.0. One way of higher education to adjust the development of Science and Technology in the era of industry 4.0 is by enriching the curriculum. Curriculum enrichment can be done by adding a new course, the Image Processing course. Image Processing is a course in Electrical Engineering which discusses data processing and analyze data in the form of images to be used as important information as requested. Image processing courses are widely used in daily life, implementation of image processing courses are found in smartphones, parking systems, medical, television and many others that utilize image processing subjects. The characteristics of this study compared two different groups: the Non-LPTK University (Lembaga Pendidikan Tenaga Kependidikan/ Educaitonal Institutions of Educatinal Staff) with the LPTK University to looking for characteristics in covering different subjects with the characteristics of vocational education, but it is related to the characteristics of vocational education in considering matching subjects with digital characteristics in the field of vocational education studies. Curriculum enrichment aims to improve the quality of higher education learning which leads to improve the quality of graduates. The researcher used a qualitative research with a comparative method ex post facto. This research is expected to be a pattern for other universities in applying curriculum enrichment methods.